Do healthy preterm children have behavior problems? - Pérez-Pereira, Miguel; Baños, Lua (Anales de Psicología / Annals of Psychology, 2019)
Background/Objective. In this study, the behavior problems of healthy preterm and full-term children will be compared. The effect of environmental and neonatal conditions on the rate of behavior problems, with special attention to maternal depression and parental stress, will also be studied. Previous studies found significantly higher prevalence rates of total problems in preterm children. Most of these studies were carried out with preterm children under 32 weeks of gestational age. In contrast, some studies carried out with moderately preterm children found no significant difference. Method. We assessed 108 low risk preterm children and 33 full-term children through the Child Behavior Checklist when they were 5 years-old. Their mothers` stress and depression were also assessed. Results. No significant difference was found between the preterm and the full-term groups for overall, internalizing or externalizing behavior problems, or for more fine-grained behavior problems such as anxiety, attention or aggression problems. No effect of gestational age on the rate of behavior problems was found. In contrast maternal stress, but not maternal depression, was a strong predictor of behavior problems. Conclusions. These results indicate that behavior problems are not characteristic of preterm children as a group, but only of very or extremely preterm children.